Walled cosmopolitanization: how China's Great Firewall mediates young urban gay men's lives. Issue 2 (13th January 2023) - Song, Lin; Wu, Shangwei
Abstract: This article explores the role of censorship as a communication technology in shaping experiences of cosmopolitanization. Drawing on interviews with urban Chinese gay men who circumvent the country's Great Firewall, the article studies how censorship shapes people's media choices, practices, and social outlooks. It presents three findings. First, censorship produces a domesticated media ecology characterized by controlled exchanges with the outside world, constructing the perceived "localness" and "foreignness" of media artifacts. Second, censorship creates an exclusive "cosmopolitan digital class" that establishes a hierarchy of desirability based on people's media practices. Third, censorship promotes a paradoxical intertwining of cosmopolitanization and encapsulation, popularizing a mindset that is at once open—willing to move across the Wall and access alternative information—and closed: subscribing to territorial understandings of selfhood. Based on these findings, the article proposes the concept of "walled cosmopolitanization" to describe the vulnerability of the cosmopolitan self in censored environments. Lay Summary: This article looks at how censorship as a communication technology influences people's cosmopolitan experiences and outlooks. The article draws on 77 semi-structured interviews with urban Chinese gay men who are used to circumventing the country's Great Firewall—its main censorship mechanism—and are often seen as the ideal cosmopolitan who embraces an open, global outlook. We have three findings. First, we find that censorship produces a local media landscape by blocking prominent international media outlets. By doing so, it decides people's media choices and constructs cultural imaginations of "local" and "foreign" media ecologies. Second, we argue that censorship creates a class distinction based on people's media practices: Those who can circumvent censorship restrictions are regarded as part of a "cosmopolitan digital class, " whereas those who cannot or do not become the "not-so-cosmopolitans." Last, we point out that two tendencies coexist in China's censored media environment: Although Chinese gay men want to move across the Great Firewall and access alternative global information, they also remain characteristically local and closed in their self-understanding and political outlook. Based on these findings, we propose "walled cosmopolitanization" to describe how a cosmopolitan self is lived out in censored environments.